Discrepancies between F‐18‐FDG PET/CT findings and conventional imaging in Langerhans cell histiocytosis. Issue 4 (14th January 2021) - Ferrell, Justin; Sharp, Susan; Kumar, Ashish; Jordan, Michael; Picarsic, Jennifer; Nelson, Adam
Abstract: Background: Accurate risk stratification of Langerhans cell histiocytosis (LCH) is essential as management can range from conservative in single system, low risk for central nervous system (CNS) involvement lesions to intensive chemotherapy for multisystem or high‐risk disease. Additionally, being able to differentiate metabolically active from inactive lesions is essential for both prognostic reasons and to avoid potentially unnecessary treatment. Methods: A retrospective review was performed on all patients with histopathology‐confirmed LCH at Cincinnati Children's Hospital Medical Center (CCHMC) between 2009 and 2019. Results: One hundred seven positron emission tomography (PET)/computerized tomography (CT) images were included in the review. A discrepancy between PET/CT and conventional imaging occurred on 53 occasions. On 13 occasions, increased uptake was observed on PET in an area with no identifiable lesion on conventional imaging. On 40 occasions, lesions were found on conventional imaging where no increased uptake was observed on PET. On eight skeletal surveys, three other radiographs, four diagnostic CTs, five localization CTs, and one bone scan, no lesion was identified in an area with increased fluorodeoxyglucose (FDG) uptake. This occurred exclusively in bone. On nine skeletal surveys, one other radiograph, four diagnostic CTs, six localization CTs, 19 magnetic resonance imaging (MRI) scans, and one bone scan, a lesion was identified in a location without increased FDG uptake. This occurred in bone, CNS, and lungs. Conclusion: F‐18‐FDG PET/CT is vital in the evaluation of LCH lesions given its ability to detect LCH lesions not detectable on conventional imaging modalities, as well as its ability to distinguish metabolically active from inactive disease. MRI and diagnostic CT are still useful adjunctive tests for identification of CNS and lung lesions.